(untitled) (MAUSAM, 1961)
The lag coefficient of the bimetal thermometer element as used in chronometric radiosonde of India Meteorological Department has been calculated with the help of the difference in temperatures obtained from a radiosonde during its ascent and descent. The average lag in the recorded temperature has also been calculated.